The RECITE Study: A Canadian Prospective, Multicenter Study of the Incidence and Severity of Residual Neuromuscular Blockade. Issue 2 (April 2016) - Fortier, Louis-Philippe; McKeen, Dolores; Turner, Kim; de Médicis, Étienne; Warriner, Brian; Jones, Philip M.; Chaput, Alan; Pouliot, Jean-François; Galarneau, André
Abstract : Surv Anesthesiol 2016;60(2):75–75 Postoperative residual neuromuscular blockade (RNMB), at normalized train-of-4 (TOF) ratios of less than 0.9, is associated with increased risk of aspiration, airway obstruction, hypoxia, pharyngeal/esophageal complications, and prolonged postanesthesia care unit stay. Residual neuromuscular blockade incidence has not been examined before in Canada, but can range from 26% to 88%, depending on various factors.